Recognizable neonatal clinical features of aplasia cutis congenita - Ingrid Anne Mandy Schierz; Mario Giuffrè; Antonello Del Vecchio; Vincenzo Antona; Giovanni Corsello; Ettore Piro (BMC, 2020)
Abstract Background Aplasia cutis congenita (ACC), classified in nine groups, is likely to be underreported, since milder isolated lesions in wellbeing newborns could often be undetected, and solitary lesions in the context of polymalformative syndromes could not always be reported. Regardless of form and cause, therapeutic options have in common the aim to restore the deficient mechanical and immunological cutaneous protection and to limit the risk of fluid leakage or rupture of the exposed organs. We aimed to review our institutional prevalence, comorbidities, treatment and outcome of newborns with ACC. Methods We conducted a retrospective study including all newborns affected by ACC and admitted at the University Mother-Child Department from October 2010 to October 2019. Anthropometric and clinical characteristics of ACC1 versus a non-isolated ACC group were analyzed. Results We encountered 37 newborns, 16 with ACC1 versus 21 with non-isolated ACC. The incidence rate of 0.1% in ACC1 was higher than expected, while 19% of cases showed intrafamilial autosomal dominant transmission. Higher birth weight centile, though lower than reference population, being adequate for gestational age, normal Apgar score and euglycemia characterizing ACC1 resulted associated to a rapid tissue regeneration. Non-isolated ACC, in relation to concomitant congenital anomalies and higher prematurity rate, showed more surgical and medical complications along with the risk of neonatal death. Specifically, newborns with ACC4 were characterized by the frequent necessity of abdominal wall defect repair, responsible for the occurrence of an abdominal compartment syndrome. Conclusion Prompt carefully assessment of the newborn with ACC in order to exclude concomitant other congenital malformations, provides clues to the underlying pathophysiology, and to the short-term prognosis. Family should be oriented toward identification of other family members affected by similar pathology, while obstetric history should exclude initial multiple pregnancy with death of a co-twin, placental anomalies and drug assumption. Molecular-genetic diagnosis and genetic counseling are integrative in individualized disease approach.